(b-6)(b+3)
use FOIL:
b*b
b*3
-6*b
-6*3
add them together to get:
b^2 - 3b - 18
Multiplying Binomials
(b-6)*(b+3)
2 answers
You distribute the first set of brackets.
When you have equations like this you should pretend there are no brackets around the first equation.
b-6 (b+3)
first you distribute b into the brackets.
(b)(b) = b^2
then b to 3
(b)(3) = 3b
then you distribute the -6 to both...
(-6)(b) = -6b
then -6 to 3...
(-6)(3) = -18
then you add them together...
b^2-3b-18
:)
When you have equations like this you should pretend there are no brackets around the first equation.
b-6 (b+3)
first you distribute b into the brackets.
(b)(b) = b^2
then b to 3
(b)(3) = 3b
then you distribute the -6 to both...
(-6)(b) = -6b
then -6 to 3...
(-6)(3) = -18
then you add them together...
b^2-3b-18
:)